The effects of rinsing red beet root (beta vulgaris L.) juice on streptococcus sp. dental plaque - Dyah Setyorini; Yani C. Rahayu; Tita Sistyaningrum (DiscoverSys Inc., 2017)
Objective : The early attachment process of plaque formation is dominated by Streptococcus sp. Chemical antiplaque agent can optimize plaque control.Material and Methods : Materials of antiplaque have side effects, so it is necessary to do research of alternative antiplaque materials. One of them use red beet root because contain some antibacterial substance. The aim of this study was examine the effectiveness of rinsing red beetroot juice to Streptococcus sp. on dental plaque.Results : This study was a quasi-experimental research with the post test only control group design. Subjects were 27 students from Faculty of Dentistry, University of Jember who fulfilled the criteria, have been scalled, and given the knowledge of how to rinse. The subjects were divided into three groups, and instructed to rinse for 30 seconds using chlorhexidine gluconate 0.2%, distilled water, and red beet root juice. Plaque were taken at the buccal maxillary first molar. Plaque were diluted and planted on streptococcus media for 24 hours, the number of colonies counted using colony counter. Analysis of One-Way ANOVA have significance 0.000, means decreased the number of Streptococcus sp.Conclusion : Rinsing red beet root juice was effective to decrease the number of Streptococcus sp. on dental plaque.